PENGARUH PUZZLE NATURAL SCIENCE BERBANTUAN AI MELALUI PBL MENINGKATKAN LITERASI SAINS SISWA KELAS V DI SEKOLAH DASAR - Saras, Yetti Yuni; Fatih, Mohamad; Alfi, Cindya (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to examine the effect of artificial intelligence (AI)-based puzzle media integrated with the Problem-Based Learning (PBL) model on the science literacy of fifth-grade students at SDN Gadungan 1, Blitar Regency. The research employed a quantitative method with a quasi-experimental design, involving an experimental group using AI-based puzzle media and a control group using conventional learning methods. Data were collected through interviews, questionnaires, and pre-test and post-test assessments. Data analysis was carried out using descriptive and inferential statistics, including a t-test. The results showed that the use of AI-based puzzle media through the PBL model significantly improved students’ science literacy compared to conventional learning methods. The experimental class achieved a higher average post-test score of 80.25, compared to the control group's average of 67.92. T-test calculations showed that the calculated t-value was greater than the critical t-value, thus H? was rejected and H? was accepted. This indicates a significant difference between the control and experimental groups. Based on these findings, it can be concluded that the use of interactive learning media such as AI-based puzzles can effectively enhance students’ conceptual understanding and learning motivation.